1996
DOI: 10.1021/ma960023r
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Number of Active Sites for Olefin Polymerization Catalyzed over Metallocene/MAO Using the CO Inhibition Method

Abstract: For a determination of the active site concentrations, [C*], the simultaneous kinetics and inhibition method using CO as a catalyst inhibitor were examined. It is noticed that this evaluation method is not quantitatively exact because MAO-activated alkyl Zr sites exist in dynamic equilibrium between dormant states and a chain propagating site and because some CO molecules coordinate even to inactive species. The number of active sites was evaluated on the assumption that two molecules of CO coordinate to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…This decreased polymerization rate was not recovered during polymerization. This phenomenon was also observed in the early transition metal olefin catalyst system [9]. Our group reported that CO affected steep decrease of ethylene polymerization rates on Cp 2 ZrCl 2 /MAO system and ethylene/ propylene copolymerization rates on rac-Me 2 Si(Ind) 2 ZrCl 2 / MAO system [9].…”
Section: Characterizationsupporting
confidence: 54%
See 1 more Smart Citation
“…This decreased polymerization rate was not recovered during polymerization. This phenomenon was also observed in the early transition metal olefin catalyst system [9]. Our group reported that CO affected steep decrease of ethylene polymerization rates on Cp 2 ZrCl 2 /MAO system and ethylene/ propylene copolymerization rates on rac-Me 2 Si(Ind) 2 ZrCl 2 / MAO system [9].…”
Section: Characterizationsupporting
confidence: 54%
“…Simultaneous kinetic and inhibition method was developed by Caunt, Tait and coworkers [6,7]. A small amount of suitable inhibitor was injected into polymerization run and decrease in the overall rate of polymerization were measured simultaneously as well as the amount of inhibitor adsorbed [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…16 Chemically, a-olefins are thought to participate in the formation of new catalyst sites and/or the activation of dormant sites 17,18 and in the increase of the propagation rate constant. 19,20 Ethylene/a-olefin synergism seems to occur only in nonhomogeneous polymerization systems, that is, polymerization over supported catalysts 21 or initially homogeneous systems in which the polymer formed is insoluble in the solvent and precipitates out of the solution. 11,22 When the polymer precipitates from an initially homogeneous system, the active center becomes encapsulated in the precipitated polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Metallocene cations are subject to equilibria between catalytically active and inactive forms, complicating the quantification of active-site concentrations (190). For example, a kinetic model for ethylene polymerization by constrained geometry catalysts requires activation and deactivation rates, and a trigger mechanism (191).…”
Section: Deactivation and Reactivationmentioning
confidence: 99%